The Influence of Gamification and Application-Based Loyalty Systems on Customer Satisfaction on E-Commerce Platforms: Pengaruh Gamifikasi dan Sistem Loyalitas Berbasis Aplikasi terhadap Kepuasan Pelanggan pada Platform E-Commerce - Joelianti Dwi Supraptiningsih; Felina Young (Jurnal Bisnis dan Ekonomi, 2025)
Abstract : Objective : This study aims to examine the effect of gamification on customer satisfaction and loyalty systems. The research seeks to understand how the implementation of interactive game elements—such as rewards, points, and challenges—can influence customers’ satisfaction and strengthen their loyalty toward a brand or platform. Methodology : The research applies a quantitative approach using survey methods with 120 respondents who actively use e-commerce applications. Data analysis was carried out using SEM Model with PLS. Research Results: The results indicate that gamification positively and significantly affects both customer satisfaction and loyalty systems, and that the loyalty system also contributes to higher customer satisfaction. These findings suggest that integrating gamification into loyalty strategies can effectively enhance customer engagement and long-term loyalty. The study highlights the importance of designing enjoyable, rewarding, and interactive customer experiences as a strategic approach to improving satisfaction and retention. Keywords: Gamification; Loyalty System; Customer Satisfaction; E-Commerce